Effects of Direct Instruction Supported by Algebrator on Learning Outcomes in Linear Equation Systems - Marajo, Suci Nurjanna Sultan; Sulistyaningsih, Murni; Sumarauw, Sylvia Jane Annatje (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Students’ understanding of systems of linear equations in two variables is often limited due to the abstract nature of the topic and the requirement for logical and systematic reasoning skills. To address this issue, an appropriate instructional model supported by effective learning media is needed. This study aimed to examine the effect of the Direct Instruction learning model supported by Algebrator on students’ learning outcomes in systems of linear equations. This study employed a quasi-experimental method using a control group pretest–posttest design. The participants were eighth-grade students at a public Islamic junior high school. The sample consisted of two classes, with 25 students in the experimental group and 25 students in the control group. The experimental group was taught using the Direct Instruction model supported by Algebrator, while the control group received conventional instruction without technological media. Data were analyzed using descriptive statistics and an independent samples t-test at a significance level of 0.05. The results showed that the mean posttest score of the experimental group was 83.44, which was higher than that of the control group, which obtained a mean score of 76.76. The t-test results indicated a significant difference between the two groups (t = 2.35, p < 0.05). These findings demonstrate that students taught using the Direct Instruction model supported by Algebrator achieved significantly better learning outcomes than those taught using conventional methods. This study indicates that the integration of technological learning media such as Algebrator can effectively enhance students’ understanding and learning outcomes in mathematics, particularly in systems of linear equations. The findings provide empirical support for the use of technology-assisted Direct Instruction in mathematics classrooms.